Cholestatic Jaundice as a Result of Combination Designer Supplement Ingestion. (July 2013) - Vilella, Antonia L; Limsuwat, Chok; Williams, Dustyn R; Seifert, Charles F
OBJECTIVE: To report a case of cholestatic jaundice as a result of combination herbal and designer supplement use. CASE SUMMARY: A 50-year-old Hispanic male presented to the hospital with a 1-week history of significant painless jaundice; total bilirubin on admission was 29.4 mg/dL. He reported use of both herbal (creatine and whey protein) and designer (Incredible Bulk and Spartan 45) supplements concurrently for approximately 2 months. Upon admission, all supplements were discontinued and multiple laboratory and diagnostic tests were ordered. On day 6 of his hospital admission, a liver biopsy was performed, the results of which indicated drug-induced hepatotoxicity. On day 9 he was discharged with prescriptions for ursodeoxycholic acid and hydroxyzine. Three months post hospital discharge, the patient continued to be supplement-free and bilirubin had decreased substantially. DISCUSSION: Anabolic-androgenic steroids are capable of causing hepatotoxicity, and multiple cases reported in the literature support this. A case report described hepatotoxicity secondary to both creatine and whey protein consumption, and several reports have described liver damage secondary to designer supplement use. To our knowledge, this is the first case to describe hepatotoxicity as a result of combination herbal and designer supplement use. The Roussel Uclaf Causality Assessment Method (RUCAM) score for drug-induced hepatotoxicity indicated a highly probable correlation between the use of combination supplements and cholestatic jaundice. CONCLUSIONS: Health care professionals need to be aware of complications associated with designer supplement use and should be able to identify patients who would benefit from education on herbal and designer supplement use.